2021
DOI: 10.1017/jns.2021.60
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet and body composition of breast-feeding mothers: the potential role of unsaturated fatty acids

Abstract: A paucity of evidence is available regarding the impact of diet's quality during pregnancy and lactation on the body composition of breast-feeding mothers. The purpose of the present study was to evaluate the association between maternal degree of adherence to the Mediterranean diet (MD) and body composition measures specifically those relating to body fat, in the lactation period. A cross-sectional study on healthy mothers of full-term babies has been conducted. At 30 ± 10 d after delivery, anthropometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Concerning the potential impact of higher consumption of OA, it is interesting to mention the results found regarding the Mediterranean diet (MD) intake, given its characteristic contribution of olive oil, unlike other diets. It has been shown that adherence to MD is associated with lower fat mass in breastfeeding mothers [38] and can impact plasma levels of miRNAs related to metabolic syndrome [39]. However, little is known about the influence of this diet on milk bioactive compounds and metabolic programming.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the potential impact of higher consumption of OA, it is interesting to mention the results found regarding the Mediterranean diet (MD) intake, given its characteristic contribution of olive oil, unlike other diets. It has been shown that adherence to MD is associated with lower fat mass in breastfeeding mothers [38] and can impact plasma levels of miRNAs related to metabolic syndrome [39]. However, little is known about the influence of this diet on milk bioactive compounds and metabolic programming.…”
Section: Discussionmentioning
confidence: 99%
“…In this aspect, breastfeeding can reduce excess maternal weight gain during pregnancy and can also decrease the mother’s likelihood of developing breast and ovarian cancers, hypertension, and insulin-independent diabetes [ 35 , 36 ]. Another study also revealed that higher adherence to the MD across gestational and breastfeeding periods has been shown to reduce the gain of excess body weight which was obtained during pregnancy, decreasing the risk for mothers of being overweight or obese in the first years following delivery [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level of oleic acid, a high MUFA in breast milk, is associated with a higher amount of MUFA intake than other fatty acids, especially those from olive oil. [ 15 17 48 ]…”
Section: Discussionmentioning
confidence: 99%